Prompts for Language Learners: A Practical Guide to Using DeepSeek as a Dictionary - Zhong, Ai (Lexikos, 2025)
Nowadays, AI models are capable of generating lexicographic content that is as good as that produced by traditional dictionaries. Meanwhile, using different prompts can return disparate results. Considering this, this article tests several prompts to demonstrate to language learners how to use a generative AI model as a dictionary. From a practical point of view, learners should improve their prompt crafting and fine-tuning skills in order to obtain well-reasoned and well-structured outputs from AI. Keywords: generative AI, language model, DeepSeek, learner’s dictionary, lexicographic productivity, prompt engineering